Compound Heterozygosity in a Family with Protein C Deficiency Illustrating the Complexity of the Underlying Molecular Mechanism - Gandrille, Sophie; Jude, Brigitte; Alhenc-Gelas, Martine; Millaire, Alain; Aiach, Martine (Thrombosis and Haemostasis, 1993)
The association of two missense mutations, a Leu 223 to Phe and an lie 403 to Met, is described in a family presenting with various protein C deficiency phenotypes. In this family, two subjects were compound heterozygotes with protein C levels of about 25%, the other members being heterozygous for only one of the mutations. The Leu 223 to Phe mutation was also found in 9 members of 3 other families and, in all cases but one, resulted in protein C levels below 60% associated with a high incidence of thrombotic complications. The other mutation, an lie 403 to Met, was identified in those of the family’ members who presented with borderline protein C concentrations. In such a family, the genomic DNA analysis represents the only way to differentiate between the genetic status of each family member. The results highlight the importance of the genotype determination and the poor discriminative power of the plasma assays currently used.